INTER-ETHNIC COMMUNICATION, TRANSFORMATION OF TASTES AND FASHIONS - Сильчук, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article investigates the modern trend of communication of civilizations, international exchange and inter-state integration.